Understanding the characteristics of cut-off lows over the Western Cape, South Africa - Abba, Omar Sabina (University of Cape Town, 2020)
Cut-off lows (COLs) are an important rainfall source in the Western Cape. While several studies have examined the devastating impacts of COLs during extreme rainfall events, little is known about the characteristics of COLs during droughts and how the characteristics are influenced by the South African complex topography. This thesis investigates the interannual variability of COLs and COL precipitation over Western Cape, with a focus on the 2015 - 2017 drought that affected the region and examines how well climate models simulate the variability. It also studies how the complex topography of South Africa influences the COLs characteristics. Four types of datasets (observation, satellite, reanalysis, and simulation) were analysed for the thesis. The observation, satellite and reanalysis data were analysed from the period 1979-2017, while two simulations were performed using a regional climate model (called WRF) and a variable grid model (called MPAS) for the period 2007-2017. A COL tracking algorithm was used to extract all the COLs that occurred in the vicinity of the Western Cape during the study periods. The Self Organising Map (SOM) was used to classify the COLs into groups based on their precipitation patterns. The upper-air data was analysed to study the characteristics of the COLs in each group. To examine the role of topography on COLs, WRF was applied to simulate three COLs over real and three idealised terrains (i.e. "no topography", "only-west-topography" and "only east topography"). The results show that, on average, the Western Cape experiences 10 COLs per year and the COLs contribute about 11% of the annual precipitation over the province, although with a large interannual variability. In 2015 and 2016, the COLs occurred more frequently than normal, with more than normal precipitation contribution, thereby reducing the drought severity in the two years. Contrarily, in 2017, the COL frequency and precipitation contribution were less than normal, because COLs were mainly seen further south. Nevertheless, we found that an increase in annual COL frequency does not always lead to an increase in the annual COL precipitation, because the COLs produce different amounts of precipitation. More than 45% of the COLs over the Western Cape produces little or no precipitation. The SOM results reveal that the spatial distribution of COL iv precipitation can be grouped into four major patterns. The first pattern indicates precipitation over the entire Western Cape while the second shows little or no precipitation; the third and fourth patterns feature precipitation over south-east coast and south-west coast, respectively. The major difference between the first pattern (i.e. wet cols) and the second pattern (dry COLs) is that while the wet COL is associated with a southward transport of warm and moist tropical air towards the Western Cape, the dry COL is not. Hence, the contrast between the warm and cold air mass is weaker in dry COLs than in its wet counterpart. The models (WRF and MPAS) capture the seasonal and annual climatologies of COLs and their precipitation. However, they do not always capture the inter-annual variability, with WRF outperforming MPAS in general and during the drought period. Both models represented all the COL precipitation patterns well but under-estimated the frequency of dry COLs throughout the seasons. However, the models were able to simulate the general observed differences between dry and wet COLs. WRF simulation shows that topography influences the precipitation, track, formation and vertical structure of COLs. Topography provides the additional forcing needed for COL formation. The results of this study may be applied to improve monitoring and prediction of extreme rainfall events over the Western Cape.